Associations of sodium intake with central hemodynamics and changes in vascular structure and function at high altitude localities. (25th November 2020) - Zhang, Z; Chen, X
Abstract: Objectives: To investigate the associations of sodium intake with central hemodynamics and changes in vascular structure and function at high altitude localities. Methods: A total of 383 Buddhists were enrolled in four temples with an average elevation of 3, 800 meters from December 2018 to January 2019. Estimated 24-hour urinary sodium excretion was measured by the Kawasaki formula using the urinary sodium/creatinine ratio of the second fasting spot urine in the morning. Central hemodynamics, including central systolic blood pressure (CSBP), central diastolic blood pressure (CDBP), central pulse pressure (CPP), central mean arterial pressure (CMAP), augmentation pressure (AP), augmentation index (AI), were evaluated by applanation tonometry using the SphygmoCor analyzer. Vascular structure and function were quantified by carotid intima media thickness (cIMT) and brachial ankle pulse wave velocity (BaPWV), respectively. Pearson correlation and multiple linear regression were used to analyze the associations between 24h urinary sodium with central arterial hemodynamic parameters, cIMT and BaPWV. Results: The estimated 24h urinary sodium excretion of the Buddhists in such area was (5.26±1.61)g and the estimated salt intake was (13.36±4.09)g. There was no significant correlation between 24h urinary sodium with CDBP, AP and cIMT (P>0.05). After adjusting for gender, age, CSBP, body mass index (BMI), fasting blood glucose (FBG), estimated glomerular filtration rate (eGFR), triglycerides (TG), high density lipoprotein (HDL) and low density lipoprotein (LDL), the estimated 24h urine sodium was positively correlated with CSBP (β=1.313, P=0.018) and CPP (β=1.311, P<0.001), the estimated 24h urinary sodium was significantly negatively correlated with AIX75 and BaPWV (β=−1.124, P=0.028 and β=−37.530, P<0.001, respectively). The line graph of means across the 24h urinary sodium quartiles and the cubic fitting curve showed that the associations between 24h urinary sodium excretion with AIX75 and BaPWV presented an approximate "J" shape. Conclusions: 24h urinary sodium was positively correlated with CSBP and CPP and negatively correlated with AIX75 and BaPWV in the Buddhists in this high altitude area. The associations between 24h urinary sodium with AIX75 and BaPWV resembled a "J" shape. Funding Acknowledgement: Type of funding source: None